Effects of transforming growth factor-beta on murine astrocyte glutamine synthetase activity. Implications in neuronal injury. - Chao, C C; Hu, S; Tsang, M; Weatherbee, J; Molitor, T W; Anderson, W R; Peterson, P K (The Journal of Clinical Investigation, 1992)
Cytokines have been implicated in the pathogenesis of a number of brain diseases in which neurological dysfunction has been attributed to a change in amino acid neurotransmitter metabolism. In the present in vitro study, we investigated the effects of cytokines on astrocyte glutamine synthetase (GS) activity and subsequently on N-methyl-D-aspartate (NMDA) receptor-mediated neurotoxicity. Proinflammatory cytokines IL-1 alpha, IL-1 beta, and IL-6 at a concentration of 20 ng/ml did not affect GS activity; however, tumor necrosis factor-alpha inhibited this activity by 20% in mixed neuronal/astrocyte cultures. Treatment for 24 h with transforming growth factor (TGF)-beta 1 or -beta 2 inhibited up to 60% GS activity. TGF-beta 2 also inhibited GS in enriched astrocyte cultures with an ED50 of 10 pg/ml. Antibodies specific to TGF-beta 2 blocked this effect. Treatment of astrocytes with TGF-beta 2 (250 pg/ml) resulted in markedly dilated rough endoplasmic reticulum. Since astrocyte GS may play a protective role in NMDA receptor-mediated neurotoxicity, we treated mixed neuronal/astrocyte cultures with TGF-beta 2 (250 pg/ml) and found a threefold potentiation of NMDA receptor-mediated neurotoxicity. These data suggest that TGF-beta impairs astrocyte GS function and enhances neurotoxicity, thus providing insight into understanding one mechanism of cytokine-mediated central nervous system disease. Images